Application of artificial intelligence language model ChatGPT in higher education - Zvonimir Klarin; Tea Livaić (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
The growing trend of using artificial intelligence tools in education, such as language models for generating natural text, brings numerous new possibilities and challenges for educational institutions. With the potential for personalized learning, improved administrative processes, and advancements in research, the application of artificial intelligence in education opens doors to innovative teaching methods and provides new perspectives for the development of educational systems. In the context of rapid technology development and increasing integration of artificial intelligence into everyday life, it is important to understand how these changes are reflected in the educational sector. This particularly pertains to the use of the ChatGPT artificial intelligence tool in the learning and teaching process. The aim of this paper is to explore the level of usage of the ChatGPT artificial intelligence tool among students and teachers at the Šibenik University of Applied Sciences. The paper presents the results of two survey questionnaires. The first questionnaire was intended for students, while the second one was directed towards academic teachers. The results revealed that the majority of students at the Šibenik University of Applied Sciences are familiar with and use ChatGPT, and they rate the received responses as highly useful, but there are different opinions regarding trust in those responses. On the other hand, academic teachers are acquainted with ChatGPT, use it for various purposes, but there is diversity in their attitudes towards trusting ChatGPT’s responses. It is important to note that the majority of academic teachers do not encourage students to use ChatGPT and have not taught them about its usage.